HUBUNGAN PROFESIONALISME DENGAN KONSEKUENSINYA: KOMITMEN ORGANISASIONAL, KEPUASAN KERJA, PRESTASI KERJA, DAN KEINGINAN BERPINDAH - JANTJE EDUARD LEKATOMPESSY (Jurnal Bisnis dan Akuntansi, 2003)
This study purposed to get empirical evidence about effect of the professionalism and its consequences: corganizational commitment, job satisfaction, job performance, and turnover intentions to accountant that work at public accounting firm. Data collected with survey method. Respondent consist of 143 professional accountant staff that in work at public accounting firm, at well that position as partner, manager, supervisor, senior accountingl, and junior accounting in the largely public accounting firm and other in five big city of Java Island. Research data were analyses by using regression technique. The result showed that the effect of professionalism with its consequences: organizational commitment, job satisfaction, job performance, and turnover intentions. With the other word, professionalism to have influence positively and significant to an organizational commitment, job satisfaction, job performance, and negatively influenced with turnover intentions. Its be as accountants who have highly professionalism action will had organizational commitment, job satisfaction, and most higher job performance, and will be have of low turnover intentions. This study also to proved that experience to had influence positively and significant with professionalism, in the meaning that accountants who have widely experience will be have more high professionalism action.